Flexibilitet eller friktion? Om inflytande över arbetstiden och konfikten mellan arbete och familj (Sociologisk Forskning, 2004)
Flexible working time, understood as the possibility for employees to adjust the working schedule to their own needs, is portrayed as a way to reduce friction between paid work and family. However, flexibility could also be a source of stress, as the responsibility to synchronize the two spheres is left to the individual. In either case, flexibility might have important effects on gender equality.The aim of this article is to explore the effect of flexible working time on work/family conflict as well as on other aspects of life outside the workplace. Data comes from a sample of Swedish employees in healthcare, manufacturing and finance (n = 1836). The results show that flexible working hours has positive effects on the ability to meet friends and relatives and to engage in hobbies, but does not reduce work/family conflict. However the degree of flexibility is also important: a high degree of flexibility increases work/family conflict, as this flexibility comes with a higher position and presumes an adjustment of working time to the needs of the organisation. In sum, the beneficial effects of flexible working hours could be called into question as long as flexibility is conditioned on high demands from the organisation.
Keywords: flexible working time; gender; work/ family conflict